Lymphotoxins Serve as a Novel Orchestrator in T1D Pathogenesis - Liu, Shi-Wei; Sun, Fei; Rong, Shan-Jie; Wang, Ting; Wang, Cong-Yi (Frontiers in Immunology, 2022)
Type 1 diabetes (T1D) stems from pancreatic β cell destruction by islet reactive immune cells. Similar as other autoimmune disorders, there is no curative remedy for T1D thus far. Chronic insulitis is the hallmark of T1D, which creates a local inflammatory microenvironment that impairs β cell function and ultimately leads to β cell death. Immune regulation shows promise in T1D treatment by providing a time window for β cell recovery. However, due to the complex nature of T1D pathogenesis, the therapeutic effect of immune regulation is often short-lasting and unsatisfying in monotherapies. Lymphotoxins (LTs) were first identified in 1960s as the lymphocyte-producing cytokine that can kill other cell types. As a biological cousin of tumor necrosis factor alpha (TNFα), LTs play unique roles in T1D development. Herein in this review, we summarized the advancements of LTs in T1D pathogenesis. We particularly highlighted their effect on the formation of peri-islet tertiary lymphoid organs (TLOs), and discussed their synergistic effect with other cytokines on β cell toxicity and autoimmune progression. Given the complex and dynamic crosstalk between immune cells and β cells in T1D setting, blockade of lymphotoxin signaling applied to the existing therapies could be an efficient approach to delay or even reverse the established T1D.